2022
DOI: 10.1186/s10194-022-01514-9
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3, randomised, placebo-controlled study of erenumab for the prevention of chronic migraine in patients from Asia: the DRAGON study

Abstract: Abstact Background DRAGON was a phase 3, randomised, double-blind, placebo-controlled study which evaluated the efficacy and safety of erenumab in patients with chronic migraine (CM) from Asia not adequately represented in the global pivotal CM study. Methods DRAGON study was conducted across 9 Asian countries or regions including mainland China, India, the Republic of Korea, Malaysia, the Philippines, Singapore, Taiwan, Thailand, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Out of 19 111 initial records after removal of duplicates, 18 777 were excluded during title and abstract screening. Three-hundred and thirty-four records were assessed for eligibility and 59 articles reporting data from 33 trials were included after full text assessment (see online supplemental appendix 2 for excluded studies) 19–57. Although many of these linked articles were cited, we only used the main trial paper for the main citation, as the other linked papers only reported some subgroup analyses, were either repetitive or combined the data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 19 111 initial records after removal of duplicates, 18 777 were excluded during title and abstract screening. Three-hundred and thirty-four records were assessed for eligibility and 59 articles reporting data from 33 trials were included after full text assessment (see online supplemental appendix 2 for excluded studies) 19–57. Although many of these linked articles were cited, we only used the main trial paper for the main citation, as the other linked papers only reported some subgroup analyses, were either repetitive or combined the data.…”
Section: Resultsmentioning
confidence: 99%
“…The patients in each of the included studies satisfied the diagnostic criteria of chronic or episodic migraine in accordance with the International Classification of Headache Disorders 58. Nineteen RCTs included only participants with episodic migraine,19 21 36–45 47–49 51–53 55 nine RCTs enrolled participants exclusively with chronic migraine,20 22–26 29–31 35 57 and five RCTs had a mixed population of both chronic or episodic migraine participants 34 46 50 54 56. All of the RCTs were conducted across multiple centres.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations